2014
DOI: 10.1155/2014/239240
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Hepatic and Renal Functions by 2,5-Hexanedione Is Accompanied by Oxidative Stress in Rats

Abstract: 2,5-Hexanedione (2,5-HD) is the toxic metabolite of n-hexane which is widely used as solvent in numerous industries. The present study elucidated the precise mechanism of 2,5-HD in hepatorenal toxicity by determining the involvement of oxidative stress in rats. Adult male Wistar rats were exposed to 0, 0.25, 0.5, and 1% 2,5-HD in drinking water for 21 days. Exposure to 2,5-HD caused liver and kidney atrophy evidenced by significant elevation in serum aminotransferases, alkaline phosphatase, albumin, bilirubin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…Exposure of rats to fluoride at 15 mg/L of drinking water for 45 consecutive days significantly decreased the absolute weight and organo-somatic index of the kidney in the treated rats, thus indicating an overt renal toxicity in the rats. The organo-somatic index is an important index of swelling, atrophy, or hypertrophy [32]. The decrease in the kidney of fluoride-exposed rats in the present study indicates atrophy which may be due to a direct effect of fluoride on the kidney.…”
Section: Discussionmentioning
confidence: 42%
“…Exposure of rats to fluoride at 15 mg/L of drinking water for 45 consecutive days significantly decreased the absolute weight and organo-somatic index of the kidney in the treated rats, thus indicating an overt renal toxicity in the rats. The organo-somatic index is an important index of swelling, atrophy, or hypertrophy [32]. The decrease in the kidney of fluoride-exposed rats in the present study indicates atrophy which may be due to a direct effect of fluoride on the kidney.…”
Section: Discussionmentioning
confidence: 42%
“…It might be due to the formation of highly reactive radicals and subsequent lipid peroxidation induced by BE. 22,32 In conclusion, significant sero-clinical and pathological observations were associated with the sub-acute exposure of BE to rats especially at the doses of 5 mg/ kg and 3 mg/kg. Extrapolation of research findings from the laboratory to the bedside involves variables such as age, season, diet, general health, contaminant interaction, and interspecies differences in metabolism, but there exists the possibility that indigenous human population could be sensitive to BE.…”
Section: Bementioning
confidence: 88%
“…Clinical surveys and animal model experiments have revealed that raised levels of ALT and AST activities are indicative of organ damage, specifically, in pathologic and toxicologic events leading to cardiac and hepatic necrosis [29,[42][43][44] . Precisely, earlier studies had associated raised serum ALT activity with non-diabetic non-alcoholic fatty liver disease and insulin resistance [45][46][47][48][49][50] .…”
Section: Discussionmentioning
confidence: 99%
“…The hepatic tissues play a central role in the biotransformation of xenobiotics and endogenous molecules prior to their elimination from the body [26][27][28] . The biotransformation of xenobiotics in the hepatocytes may elicit the formation of noxious and highly reactive compounds or potentially toxic metabolites, which in the process of their metabolism predisposes the hepatocytes to injuries and dysfunction [29] . The renal tissues are highly specialized in ensuring delicate balance in selective excretion or retention of body biomolecules, according to their physiologic renal threshold indices [30] .…”
Section: Introductionmentioning
confidence: 99%